The wanderers - Howrey, Meg (G.P. Putnam's Sons, 2017)
"Station Eleven meets The Martian in this brilliantly inventive novel about three astronauts training for the first-ever mission to Mars, an experience that will push the boundary between real and unreal, test their relationships, and leave each of them--and their families--changed forever. In an age of space exploration, we search to find ourselves. In four years Prime Space will put the first humans on Mars. Helen Kane, Yoshi Tanaka, and Sergei Kuznetsov must prove they're the crew for the job by spending seventeen months in the most realistic simulation ever created. Retired from NASA, Helen had not trained for irrelevance. It is nobody's fault that the best of her exists in space, but her daughter can't help placing blame. The MarsNOW mission is Helen's last chance to return to the only place she's ever truly felt at home. For Yoshi, it's an opportunity to prove himself worthy of the wife he has loved absolutely, if not quite rightly. Sergei is willing to spend seventeen months in a tin can if it means travelling to Mars. He will at least be tested past the point of exhaustion, and this is the example he will set for his sons. As the days turn into months the line between what is real and unreal becomes blurred, and the astronauts learn that the complications of inner space are no less fraught than those of outer space. The Wanderers gets at the desire behind all exploration: the longing for discovery and the great search to understand the human heart"--